The physiology of adventitious roots - Steffens, Bianka; Rasmussen, Amanda (American Society of Plant Physiology, 2016)
Adventitious roots are plant roots that form from any nonroot tissue and are produced both during normal development (crown roots on cereals and nodal roots on strawberry [Fragaria spp.]) and in response to stress conditions, such as flooding, nutrient deprivation, and wounding. They are important economically (for cuttings and food production), ecologically (environmental stress response), and for human existence (food production). To improve sustainable food production under environmentally extreme conditions, it is important to understand the adventitious root development of crops both in normal and stressed conditions. Therefore, understanding the regulation and physiology of adventitious root formation is critical for breeding programs. Recent work shows that different adventitious root types are regulated differently, and here, we propose clear definitions of these classes. We use three case studies to summarize the physiology of adventitious root development in response to flooding (case study 1), nutrient deficiency (case study 2), and wounding (case study 3).